Peningkatan Value Added Activity Refiller Warehouse Lantai 2 di PT. Schneider Electrics Manufacturing Batam (SEMB) - Michael Joseph Konstantinus; Felecia Felecia (Jurnal Titra, 2023)
PT. Schneider Manufacturing Batam has high NPV cost data. NPV or non-proportional to volume, namely costs that do not provide direct added value to the product. This is shown from the data on storage hours in the 2022 period which is still a negative number with an average of -1776.83 hours/month. The condition that occurs in the field is that refillers often carry out activities that should not be important. With the current condition of the warehouse there are three operators, this number can still be reduced. This operator reduction will have an impact on reducing production costs. The method used in this research is DMAIC. Analysis using motion studies on the activities of the fillers is then classified as value-adding or non-value-adding activities. The initial average value added using the three refillers was 47% and increased by 74%, it was seen that there was an increase of 27%. The reduction in refiller operators has had a positive impact and refill operators can still work on all job desks with only two operators.